Effect of DL-Methylephedrine on Dopamine Transporter Using Positron Emission Tomography With [18F]FE-PE2I - Nogami, Tsuyoshi; Arakawa, Ryosuke; Sakayori, Takeshi; Ikeda, Yumiko; Okubo, Yoshiro; Tateno, Amane (Frontiers in Psychiatry, 2022)
Rationale Since ephedrine has a dopamine transporter (DAT) inhibitory effect similar to amphetamine, dl-methylephedrine, a derivative of ephedrine, is considered to have the characteristics of a central nervous system stimulant due to the DAT inhibitory effect. For example, the World Anti-Doping Agency categorizes dl-methylephedrine as a stimulant in the prohibited list for competitions. Assuming to have the same effect as ephedrine, the urinary concentration of dl-methylephedrine is regulated below 10 μg/mL, as is ephedrine. However, the extent to which dl-methylephedrine affects brain function is not yet fully understood. Objectives The purpose of this study was to evaluate DAT occupancy by a single oral administration of a daily dose of dl-methylephedrine using positron emission tomography (PET) with [18F]FE-PE2I to characterize its stimulatory effect on the central nervous system. Methods Nine healthy male volunteers were enrolled in the study. The experiments were designed as a placebo-controlled randomized double-blind crossover comparative study. After the first PET scan in a drug-free state, the second and third PET scans were performed with randomized dosing at 60mg of dl-methylephedrine or placebo. The plasma and urine concentrations of dl-methylephedrine were measured just before and after the PET scans, respectively. Results Mean urine and plasma concentrations of dl-methylephedrine were 13.9 μg/mL and 215.2 ng/mL, respectively. Mean DAT occupancy in the caudate was 4.4% for dl-methylephedrine and 1.2% for placebo. Mean DAT occupancy in the putamen was 3.6% for dl-methylephedrine and 0.5% for placebo. There was no significant difference of DAT occupancies between the groups. Conclusion In this study, the urinary concentration of dl-methylephedrine (13.9 μg/mL) was higher than the prohibited reference value (10.0 μg/mL), and there was no significant difference in DAT occupancy between dl-methylephedrine and placebo. These findings suggest that a clinical daily dose of dl-methylephedrine may exceed the doping regulation value according to urine concentration; however, it was considered that at least the central excitatory effect mediated by DAT inhibition was not observed at the daily dose of dl-methylephedrine.